Revealing the transfer pathways of cyanobacterial-fixed N into the boreal forest through the feather-moss microbiome - Arróniz-Crespo, María; Bougoure, Jeremy; Murphy, Daniel V.; Cutler, Nick A.; Souza-Egipsy, Virginia; Chaput, Dominique L.; Jones, Davey L.; Ostle, Nicholas; Wade, Stephen C.; Clode, Peta L.; DeLuca, Thomas H. (Frontiers in Plant Science, 2022)
Biological N2 fixation in feather-mosses is one of the largest inputs of new nitrogen (N) to boreal forest ecosystems; however, revealing the fate of newly fixed N within the bryosphere (i.e. bryophytes and their associated organisms) remains uncertain. Herein, we combined 15N tracers, high resolution secondary ion mass-spectrometry (NanoSIMS) and a molecular survey of bacterial, fungal and diazotrophic communities, to determine the origin and transfer pathways of newly fixed N2 within feather-moss (Pleurozium schreberi) and its associated microbiome. NanoSIMS images reveal that newly fixed N2, derived from cyanobacteria, is incorporated into moss tissues and associated bacteria, fungi and micro-algae. These images demonstrate that previous assumptions that newly fixed N2 is sequestered into moss tissue and only released by decomposition are not correct. We provide the first empirical evidence of new pathways for N2 fixed in feather-mosses to enter the boreal forest ecosystem (i.e. through its microbiome) and discuss the implications for wider ecosystem function.